2009
DOI: 10.1213/ane.0b013e3181b0fedb
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Paracetamol When Added to Lidocaine for Intravenous Regional Anesthesia

Abstract: The addition of paracetamol during IVRA with lidocaine decreased tourniquet pain, increased anesthesia quality, and decreased postoperative analgesic consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 16 publications
4
31
1
5
Order By: Relevance
“…In Yasser M et al study [9] using 100 mg tramadol with 3 mg/kg 0.5% lidocaine in IVRA showed significantly early onset time and delayed recovery time of sensory and motor block than lignocaine group. In Sen et al [10] study on addition of paracetamol to lignocaine 3 mg/kg in IVRA lead to early onset of motor block and delayed offset of sensory and motor block than lignocaine group. Our results were in accordance with results of these studies.…”
Section: Discussionmentioning
confidence: 97%
“…In Yasser M et al study [9] using 100 mg tramadol with 3 mg/kg 0.5% lidocaine in IVRA showed significantly early onset time and delayed recovery time of sensory and motor block than lignocaine group. In Sen et al [10] study on addition of paracetamol to lignocaine 3 mg/kg in IVRA lead to early onset of motor block and delayed offset of sensory and motor block than lignocaine group. Our results were in accordance with results of these studies.…”
Section: Discussionmentioning
confidence: 97%
“…It has some advantages for example providing a blood-free surgery site, an easy applicability, a rapid termination of the anesthetic effect when compared with general anesthesia. Some clinical studies demonstrated that the addition of analgesics to the local anesthetics during IVRA decreased tourniquet pain and increased anesthesia quality in hand and forearm surgeries [10][11][12].…”
Section: Hand and Forearm Surgerymentioning
confidence: 99%
“…10 Two control groups, one for IVRA injectate (lidocaine only) and a second for paracetamol administered systemically, were used. The authors found that the addition of paracetamol to the IVRA injectate significantly reduced patients' intraoperative pain at 20 and 30 minutes compared with control groups (p ϭ .018 and p ϭ .03, respectively).…”
Section: Pharmacologic Considerationsmentioning
confidence: 99%